Penerapan Blended Learning pada Pelajaran PPKn di SMAN 2 Sukabumi - Isep Sunandi; Abdulah Alwasili; Denih Saputra (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
This study aims to explore and analyze the implementation of blended learning in the subject of Pancasila and Citizenship Education (PPKn) at SMAN 2 Sukabumi. The research method used is a case study with a qualitative approach. Data were collected through in-depth interviews with PPKn teachers and students, observation of the learning process, and analysis of documents related to the implementation of blended learning at the school. The results show that the implementation of blended learning in PPKn at SMAN 2 Sukabumi has been meticulous and well-coordinated. PPKn teachers integrate various digital media and e-learning platforms to present learning materials and assignments. Interaction between teachers and students is enhanced through online discussion forums and video conference meetings. Blended learning provides flexibility for students, allowing them to access materials independently and learn at their own pace. However, challenges faced in the implementation include limited internet access in certain areas and adjustments for students new to online learning. This research offers valuable insights into blended learning in PPKn at SMAN 2 Sukabumi and provides implications and recommendations to enhance the effectiveness of blended learning in citizenship education. By leveraging technology and innovative teaching methods, blended learning can empower students to become more independent and engaged learners, even in challenging circumstances.